2020
DOI: 10.1212/nxg.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygous STUB1 missense variants cause ataxia, cognitive decline, and STUB1 mislocalization

Abstract: ObjectiveTo identify the genetic cause of autosomal dominant ataxia complicated by behavioral abnormalities, cognitive decline, and autism in 2 families and to characterize brain neuropathologic signatures of dominant STUB1-related ataxia and investigate the effects of pathogenic variants on STUB1 localization.MethodsClinical and research-based exome sequencing was used to identify the causative variants for autosomal dominant ataxia in 2 families. Gross and microscopic neuropathologic evaluations were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 46 publications
5
29
0
Order By: Relevance
“…Despite optimisation within this study, PCR stuttering was observed in the PCR-based assay similar to previous reports 13 , 19 , which is a standard complication when amplifying repetitive genomic sequences, and highlights the need for further optimisation of the assay. By comparison, calling from WGS files revealed a similar distribution as reported previously 33 . While it has been presented as having fewer challenges in optimisation and sequencing, calling of ‘523’ variants was an arduous process and the aforementioned study has stated that the correlation between ‘523’ calling by WGS and PCR-based methods decreases with increasing size of the ‘523’ allele 33 .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Despite optimisation within this study, PCR stuttering was observed in the PCR-based assay similar to previous reports 13 , 19 , which is a standard complication when amplifying repetitive genomic sequences, and highlights the need for further optimisation of the assay. By comparison, calling from WGS files revealed a similar distribution as reported previously 33 . While it has been presented as having fewer challenges in optimisation and sequencing, calling of ‘523’ variants was an arduous process and the aforementioned study has stated that the correlation between ‘523’ calling by WGS and PCR-based methods decreases with increasing size of the ‘523’ allele 33 .…”
Section: Discussionsupporting
confidence: 84%
“…By comparison, calling from WGS files revealed a similar distribution as reported previously 33 . While it has been presented as having fewer challenges in optimisation and sequencing, calling of ‘523’ variants was an arduous process and the aforementioned study has stated that the correlation between ‘523’ calling by WGS and PCR-based methods decreases with increasing size of the ‘523’ allele 33 .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The same phenomena also occurred to SPTBN2, causing both SCA5 and SCAR15 due to dominant and recessive mutations, respectively 120,121 . The researchers named this disease SCA48 119,[122][123][124][125][126] (Fig. 2 and Table 2).…”
Section: Neurological Diseases Caused By Chip Mutationsmentioning
confidence: 99%